ASEAN ECONOMIC INTEGRATION: TRADE CREATION OR TRADE DIVERSION FOR IMPORT OF INDONESIA MANUFACTURES? - Samsubar Saleh; Bambang Suprayitno (Universitas Islam Indonesia, 2010)
This research investigates the trade creation and trade diversion of Indonesia manufactures importfrom extra and intra ASEAN countries after ASEAN economic integration. Using regression analysis,the study suggests that Indonesia manufactures import has been diverted from extra ASEANcountries both in short run and long run. In the short run, the ASEAN economic integration doesnot result in trade creation for Indonesia manufactures import from intra-ASEAN countries. Thismight stems from the insignificant difference Common Effective Preferential Tariff (CEPT) andMost Favoured Nation (MFN) tariffs and the existence of non-tariff barriers.Keywords: Economic integration, trade creation, trade diversion, Indonesia manufacturesJEL classification numbers: F15, O14